Therapeutic Potential of GABAergic Signaling in Myelin Plasticity and Repair - Reyes-Haro, Daniel; Cisneros-Mejorado, Abraham; Arellano, Rogelio O. (Frontiers in Cell and Developmental Biology, 2021)
Oligodendrocytes (OLs) produce myelin to insulate axons. This accelerates action potential propagation, allowing nerve impulse information to synchronize within complex neuronal ensembles and promoting brain connectivity. Brain plasticity includes myelination, a process that starts early after birth and continues throughout life. Myelin repair, followed by injury or disease, requires new OLs differentiated from a population derived from oligodendrocyte precursor cells (OPCs) that continue to proliferate, migrate and differentiate to preserve and remodel myelin in the adult central nervous system. OPCs represent the largest proliferative neural cell population outside the adult neurogenic niches in the brain. OPCs receive synaptic inputs from glutamatergic and GABAergic neurons throughout neurodevelopment, a unique feature among glial cells. Neuron-glia communication through GABA signaling in OPCs has been shown to play a role in myelin plasticity and repair. In this review we will focus on the molecular and functional properties of GABAA receptors (GABAARs) expressed by OPCs and their potential role in remyelination.